Cyclotron resonant scattering feature simulations II. Description of the CRSF simulation process - Schwarm, Fritz-Walter; Ballhausen, Ralf; Falkner, Sebastian; Schoenherr, G.; Pottschmidt, K.; Wolff, M. T.; Becker, P. A.; Furst, F.; Marcu-Cheatham, D. M.; Hemphill, P. B.; Sokolova-Lapa, E.; Dauser, Thomas; et al. (Astronomy & Astrophysics, 2017)
Context. Cyclotron resonant scattering features (CRSFs) are formed by scattering of X-ray photons off quantized plasma electrons in the strong magnetic field (of the order 10(12) G) close to the surface of an accreting X-ray pulsar. Due to the complex scattering cross-sections, the line profiles of CRSFs cannot be described by an analytic expression. Numerical methods, such as Monte Carlo (MC) simulations of the scattering processes, are required in order to predict precise line shapes for a given physical setup, which can be compared to observations to gain information about the underlying physics in these systems.Aims. A versatile simulation code is needed for the generation of synthetic cyclotron lines. Sophisticated geometries should be investigatable by making their simulation possible for the first time.Methods. The simulation utilizes the mean free path tables described in the first paper of this series for the fast interpolation of propagation lengths. The code is parallelized to make the very time-consuming simulations possible on convenient time scales. Furthermore, it can generate responses to monoenergetic photon injections, producing Green's functions, which can be used later to generate spectra for arbitrary continua.Results. We develop a new simulation code to generate synthetic cyclotron lines for complex scenarios, allowing for unprecedented physical interpretation of the observed data. An associated XSPEC model implementation is used to fit synthetic line profiles to NuSTAR data of Cep X-4. The code has been developed with the main goal of overcoming previous geometrical constraints in MC simulations of CRSFs. By applying this code also to more simple, classic geometries used in previous works, we furthermore address issues of code verification and cross-comparison of various models. The XSPEC model and the Green's function tables are available online (see link in footnote, page 1).
Keywords: X-rays: binaries; stars: neutron; methods: numerical

Cyclotron resonant scattering feature simulations: I. Thermally averaged cyclotron scattering cross sections, mean free photon-path tables, and electron momentum sampling - Schwarm, Fritz-Walter; Schönherr, Gabriele; Falkner, Sebastian; Pottschmidt, Katja; Wolff, Michael; Becker, Peter A.; Sokolova-Lapa, Ekaterina; Klochkov, Dmitry; Ferrigno, Carlo; Fuerst, Felix; Hemphill, Paul F.; Marcu-Cheatham, Diana M.; et al. (Astronomy & Astrophysics, 2017)
Context. Electron cyclotron resonant scattering features (CRSFs) are observed as absorption-like lines in the spectra of X-ray pulsars. A significant fraction of the computing time for Monte Carlo simulations of these quantum mechanical features is spent on the calculation of the mean free path for each individual photon before scattering, since it involves a complex numerical integration over the scattering cross section and the (thermal) velocity distribution of the scattering electrons. Aims. We aim to numerically calculate interpolation tables which can be used in CRSF simulations to sample the mean free path of the scattering photon and the momentum of the scattering electron. The tables also contain all the information required for sampling the scattering electron's final spin. Methods. The tables were calculated using an adaptive Simpson integration scheme. The energy and angle grids were refined until a prescribed accuracy is reached. The tables are used by our simulation code to produce artificial CRSF spectra. The electron momenta sampled during these simulations were analyzed and justified using theoretically determined boundaries. Results. We present a complete set of tables suited for mean free path calculations of Monte Carlo simulations of the cyclotron scattering process for conditions expected in typical X-ray pulsar accretion columns (0:01 ≤ B/B ≤ 0.12, where B = 4.413 × 10 G, and 3 keV ≤ kT ≤ 15 keV). The sampling of the tables is chosen such that the results have an estimated relative error of at most 1=15 for all points in the grid. The tables are available online (see link in footnote, page 1
Keywords: Methods: numerical; Stars: neutron; X-rays: binaries

Looking at A 0535+26 at low luminosities with NuSTAR - Ballhausen, Ralf; Pottschmidt, Katja; Furst, Felix; Wilms, Jörn; Tomsick, John A.; Schwarm, Fritz-Walter; Stern, Daniel; Kretschmar, Peter; Caballero, Isabel; Harrison, Fiona A.; Boggs, Steven E.; Christensen, Finn E.; et al. (Astronomy & Astrophysics, 2017)
We report on two NuSTAR observations of the high-mass X-ray binary A 0535 + 26 taken toward the end of its normal 2015 outburst at very low 3-50 keV luminosities of similar to 1.4 x 10(36) erg s(-1) and similar to 5 x 10(35) erg s(-1), which are complemented by nine Swift observations. The data clearly confirm indications seen in earlier data that the source's spectral shape softens as it becomes fainter. The smooth exponential rollover at high energies seen in the first observation evolves to a much more abrupt steepening of the spectrum at 20-30 keV. The continuum evolution can be nicely described with emission from a magnetized accretion column, modeled using the compmag model modified by an additional Gaussian emission component for the fainter observation. Between the two observations, the optical depth changes from 0.75 +/- 0.04 to 0.56(-0.04)(+0.01), the electron temperature remains constant, and there is an indication that the column decreases in radius. Since the energy-resolved pulse profiles remain virtually unchanged in shape between the two observations, the emission properties of the accretion column reflect the same accretion regime. This conclusion is also confirmed by our result that the energy of the cyclotron resonant scattering feature (CRSF) at similar to 45 keV is independent of the luminosity, implying that the magnetic field in the region in which the observed radiation is produced is the same in both observations. Finally, we also constrain the evolution of the continuum parameters with the rotational phase of the neutron star. The width of the CRSF could only be constrained for the brighter observation. Based on Monte Carlo simulations of CRSF formation in single accretion columns, its pulse phase dependence supports a simplified fan beam emission pattern. The evolution of the CRSF width is very similar to that of the CRSF depth, which is, however, in disagreement with expectations.
Keywords: X-rays: binaries; pulsars: individual: A 0535+26; stars: neutron; accretion; accretion disks; stars: magnetic field

No anticorrelation between cyclotron line energy and X-ray flux in 4U 0115+634 - Müller, Sebastian; Ferrigno, C.; Kühnel, Matthias; Schoenherr, G.; Becker, P. A.; Wolff, M. T.; Hertel, Dominik; Schwarm, Fritz-Walter; Grinberg, Victoria; Obst, M.; Caballero, I.; Pottschmidt, K.; et al. (Astronomy & Astrophysics, 2013)
We report on an outburst of the high mass X-ray binary 4U 0115+634 with a pulse period of 3.6 s in 2008 March/April as observed with RXTE and INTEGRAL. During the outburst the neutron star's luminosity varied by a factor of 10 in the 3-50 keV band. In agreement with earlier work we find evidence of five cyclotron resonance scattering features at similar to 10.7, 21.8, 35.5, 46.7, and 59.7 keV. Previous work had found an anticorrelation between the fundamental cyclotron line energy and the X-ray flux. We show that this apparent anticorrelation is probably due to the unphysical interplay of parameters of the cyclotron line with the continuum models used previously, e. g., the negative and positive exponent power law (NPEX). For this model, we show that cyclotron line modeling erroneously leads to describing part of the exponential cutoff and the continuum variability, and not the cyclotron lines. When the X-ray continuum is modeled with a simple exponentially cutoff power law modified by a Gaussian emission feature around 10 keV, the correlation between the line energy and the flux vanishes, and the line parameters remain virtually constant over the outburst. We therefore conclude that the previously reported anticorrelation is an artifact of the assumptions adopted in the modeling of the continuum.
Keywords: X-rays: binaries; pulsars: individual 4U 0115+634; magnetic fields

Simulation of cyclotron resonant scattering features The effect of bulk velocity - Schwarm, Fritz-Walter; Schoenherr, G.; Kühnel, Matthias; Wilms, Jörn (2014)
X-ray binary systems consisting of a mass donating optical star and a highly magnetized neutron star, under the right circumstances, show quantum mechanical absorption features in the observed spectra called cyclotron resonant scattering features (CRSFs). We have developed a simulation to model CRSFs using Monte Carlo methods. We calculate Green's tables which can be used to imprint CRSFs to arbitrary X-ray continua. Our simulation keeps track of scattering parameters of individual photons, extends the number of variable parameters of previous works, and allows for more flexible geometries. Here we focus on the influence of bulk velocity of the accreted matter on the CRSF line shapes and positions.

Spectral and Timing Analysis of the Accretion-powered Pulsar 4U 1626-67 Observed with Suzaku and NuSTAR - Iwakiri, Wataru B.; Pottschmidt, Katja; Falkner, Sebastian; Hemphill, Paul B.; Furst, Felix; Nishimura, Osamu; Schwarm, Fritz-Walter; Wolff, Michael T.; Marcu-Cheatham, Diana M.; Chakrabarty, Deepto; Tomsick, John A.; Wilson-Hodge, Colleen A.; et al. (Astrophysical Journal, 2019)
We present an analysis of the spectral shape and pulse profile of the accretion-powered pulsar 4U 1626-67 observed with Suzaku and Nuclear Spectroscopic Telescope Array (NuSTAR) during a spin-up state. The pulsar, which experienced a torque reversal to spin-up in 2008, has a spin period of similar to 7.7 s. Comparing the phase-averaged spectra obtained with Suzaku in 2010 and with NuSTAR in 2015, we find that the spectral shape changed between the two observations: the 3-10 keV flux increased by similar to 5%, while the 30-60 keV flux decreased significantly by similar to 35%. Phase-averaged and phase-resolved spectral analysis shows that the continuum spectrum observed by NuSTAR is well described by an empirical negative and positive power law times exponential continuum with an added broad Gaussian emission component around the spectral peak at similar to 20 keV. Taken together with the observed P. value obtained from the Fermi/gamma-ray burst monitor data, we conclude that the spectral change between the Suzaku and NuSTAR observations was likely caused by an increase in the accretion rate. We also report the possible detection of asymmetry in the profile of the fundamental cyclotron line. Furthermore, we present a study of the energy-resolved pulse profiles using a new relativistic ray tracing code, where we perform a simultaneous fit to the pulse profiles assuming a two-column geometry with a mixed pencil- and fan-beam emission pattern. The resulting pulse profile decompositions enable us to obtain geometrical parameters of accretion columns (inclination, azimuthal and polar angles) and a fiducial set of beam patterns. This information is important to validate the theoretical predictions from radiation transfer in a strong magnetic field.
CRIS-Team WoS Importer:2021-10-18

The giant outburst of 4U 0115+634 in 2011 with Suzaku and RXTE: Minimizing cyclotron line biases - Kühnel, Matthias; Kreykenbohm, Ingo; Ferrigno, Carlo; Pottschmidt, Katja; Marcu-Cheatham, Diana M.; Fuerst, Felix; Rothschild, Richard E.; Kretschmar, Peter; Klochkov, Dmitry; Hemphill, Paul; Hertel, Dominik; Müller, Sebastian; et al. (Astronomy & Astrophysics, 2020)
We present an analysis of X-ray spectra of the high-mass X-ray binary 4U 0115+634 as observed with Suzaku and RXTE in 2011 July, during the fading phase of a giant X-ray outburst. We used a continuum model consisting of an absorbed cutoff power law and an ad hoc Gaussian emission feature centered around 8.5 keV, which we attribute to cyclotron emission. Our results are consistent with a fundamental cyclotron absorption line centered at similar to 10.2 keV for all observed flux ranges. At the same time we rule out significant influence of the 8.5 kev Gaussian on the parameters of the cyclotron resonant scattering feature, which are not consistent with the cyclotron line energies or the depths of previously reported flux-dependent descriptions. We also show that some continuum models can lead to artificial line-like residuals in the analyzed spectra, which are then misinterpreted as unphysically strong cyclotron lines. Specifically, our results do not support the existence of a previously claimed additional cyclotron feature at similar to 15 keV. Apart from these features, we find for the first time evidence for a He-like FeXXV emission line at similar to 6.7 keV and weak H-like FeXXVI emission close to similar to 7.0 keV.
CRIS-Team WoS Importer:2020-03-13

The goodness of simultaneous fits in ISIS - Kühnel, Matthias; Falkner, Sebastian; Großberger, Christoph; Ballhausen, Ralf; Dauser, Thomas; Schwarm, Fritz-Walter; Kreykenbohm, Ingo; Nowak, Michael A.; Pottschmidt, Katja; Ferrigno, Carlo; Rothschild, Richard E.; Martínez-Núñez, Silvia; et al. (Acta Polytechnica, 2016)
In a previous work, we introduced a tool for analyzing multiple datasets simultaneously, which has been implemented into ISIS. This tool was used to fit many spectra of X-ray binaries. However, the large number of degrees of freedom and individual datasets raise an issue about a good measure for a simultaneous fit quality. We present three ways to check the goodness of these fits: we investigate the goodness of each fit in all datasets, we define a combined goodness exploiting the logical structure of a simultaneous fit, and we stack the fit residuals of all datasets to detect weak features. These tools are applied to all RXTE-spectra from GRO 1008−57, revealing calibration features that are not detected significantly in any single spectrum. Stacking the residuals from the best-fit model for the Vela X-1 and XTE J1859+083 data evidences fluorescent emission lines that would have gone undetected otherwise.
Keywords: Data analysis; Multiple datasets; X-rays binaries

The NuSTAR X-Ray Spectrum of Hercules X-1: A Radiation-dominated Radiative Shock - Wolff, Michael T.; Becker, Peter A.; Gottlieb, Amy M.; Fuerst, Felix; Hemphill, Paul B.; Marcu-Cheatham, Diana M.; Pottschmidt, Katja; Schwarm, Fritz-Walter; Wilms, Jörn; Wood, Kent S. (Astrophysical Journal, 2016)
Keywords: methods: data analysis; radiative transfer; stars: individual: Her X-1; stars: neutron; X-rays: binaries